Rim15 Antagonistic Pleiotropy Is Responsible for Differences in Fermentation and Stress Response Kinetics in Budding Yeast - Martinez-Fernandez, C; Garcia-Mena, V; Cubillos-Riffo, F; Kessi-Perez, E; Abarca, V (Oxford University Press, 2016)
Different natural yeast populations have faced dissimilar selective pressures due to the heterogeneous fermentation substrates available around the world; this increases the genetic and phenotypic diversity in Saccharomyces cerevisiae. In this context, we expect prominent differences between isolates when exposed to a particular condition, such as wine or sake musts. To better comprehend the mechanisms underlying niche adaptation between two S. cerevisiae isolates obtained from wine and sake fermentation processes, we evaluated fermentative and fungicide resistance phenotypes and identify the molecular origin of such adaptive variation. Multiple regions were associated with fermentation rate under different nitrogen conditions and fungicide resistance, with a single QTL co-localizing in all traits. Analysis around this region identified RIM15 as the causative locus driving fungicide sensitivity, together with efficient nitrogen utilization and glycerol production in the wine strain. A null RIM15 variant confers a greater fermentation rate through the utilization of available glucose instead of its storage. However, this variant has a detrimental effect on fungicide resistance since complex sugars are not synthesized and transported into the membrane. Together, our results reveal the antagonist pleiotropic nature of a RIM15 null variant, positively affecting a series of fermentation related phenotypes, but apparently detrimental in the wild. © FEMS 2016. All rights reserved.